Suicide attempts in Estado de México: the voices of young adults and adolescents - Bernáldez Jaimes, Germán Benito; Vargas Jaimes, Claudia (Acta Universitaria, 2026)
The study used a qualitative methodology with a phenomenological-interpretative approach aimed at describing risk factors and suicidal experiences in young people and adolescents. It was structured in two phases: the first was carried out with 45 participants using a semi-structured interview to identify the motives and means of suicide attempts; in the second, eight volunteers were chosen for in-depth interviews. The results indicate that the most common motives for a suicidal act are family problems (23%) and feelings of loneliness (19%), using knives, medication, or a combination of both (76%) as the means. The narratives show a perception of emotional deprivation, fear of family reactions, altered self-esteem, feelings of instability, isolation, self-harm, and addiction. The presence of farewell behaviors or changes in usual behavior is noteworthy. Listening and parental involvement could improve interventions to prevent suicide.